2014
DOI: 10.1007/s10561-014-9483-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gestational diabetes on proliferation capacity and viability of human umbilical cord-derived stromal cells

Abstract: Stomal cells derived from Wharton's jelly of human umbilical cord (WJMSCs) are considered as the potential therapeutic agents for regeneration and are getting famous for stem cell banking. Our study aims to evaluate the effects of gestational diabetes on proliferation capacity and viability of WJMSCs. Mesenchymal stromal cells were isolated from Wharton's jelly of human umbilical cords from normal and gestational diabetic (DWJMSCs) mothers. Growth patterns of both types of cells were analyzed through MTT assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Gestational diabetes mellitus (GDM) impairs the proliferative capacity of WJMSCs. The key factor involved in GDM is excessive amount of glucose in mother which crosses freely to fetus 7 . In order to achieve maximum therapeutic benefits it is a prerequisite to optimize the culture conditions for cellular growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gestational diabetes mellitus (GDM) impairs the proliferative capacity of WJMSCs. The key factor involved in GDM is excessive amount of glucose in mother which crosses freely to fetus 7 . In order to achieve maximum therapeutic benefits it is a prerequisite to optimize the culture conditions for cellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…Many pathological conditions including diabetes mellitus are associated with hyperglycemia 5 and oxidative stress which affects the growth of stem cell 6 . It is reported that WJMSCs derived from diabetic mothers (DWJMSCs) show reduced growth rate in culture conditions as compared to normal mothers' derived WJMSCs (NWJMSCs) 7 . This study is based on finding the optimal glucose concentration for maximum growth of NWJMSCs and DWJMSCs in vitro.…”
Section: Quick Response Code Doimentioning
confidence: 99%
See 2 more Smart Citations
“…ELISA was done as reported previously [15,16]. Solid phase sandwich ELISA was done for Using a micro-titer plate reader, absorbance was taken at a wavelength of 450 nm along with 650 nm as a reference value.…”
Section: Elisamentioning
confidence: 99%